2004
DOI: 10.1159/000082834
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Capsule Endoscopy in Obscure Gastrointestinal Bleeding

Abstract: Objectives:Chronic occult blood loss from the gastrointestinal tract is a recognized major cause of iron-deficiency anemia. After conventional investigation of the upper and lower parts of the gastrointestinal tract, the source of bleeding remains unidentified in ~10% of these patients. We evaluated the diagnostic yield of capsule endoscopy from patients enrolled in clinical studies due to persistent or recurrent iron-deficiency anemia. Methods: In this large cohort study, patients with obscure gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…16,[27][28][29][30] In this study, we reported a relatively high diagnostic yield of 47.56% and 68.66% for MSCT and CE, respectively. Despite a lower overall diagnostic yield than CE, MSCT examination in our study achieved a similar diagnostic capability to CE.…”
Section: Discussionmentioning
confidence: 93%
“…16,[27][28][29][30] In this study, we reported a relatively high diagnostic yield of 47.56% and 68.66% for MSCT and CE, respectively. Despite a lower overall diagnostic yield than CE, MSCT examination in our study achieved a similar diagnostic capability to CE.…”
Section: Discussionmentioning
confidence: 93%
“…These lesions were identified by CE and were indicative of a second endoscopy. In another study [24], CE detected findings in 1% (oesophagus) and 17.8% (stomach) of patients evaluated for both obscure and overt GI bleeding. In the same study, CE missed lesions in the oesophagus (32%) and the stomach (43%), further underpinning the need of a repeat endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Obscure gastrointestinal bleeding (OGIB) is generally characterized as persistent or recurrent GIB, which cannot be identified by conventional gastrointestinal endoscopy and/or conventional radiological examinations of the small intestine (1). Pathological changes in the small intestine account for 2-10% of all causes for OGIB; however, they are poorly identified by conventional approaches.…”
Section: Introductionmentioning
confidence: 99%